Establishing the Framework for Using Photos in Art Therapy (and other Therapies) Practices - Weiser, Judy (Arteterapia. Papeles de arteterapia y educación artística para la inclusión social, 2014)
What is PhotoTherapy and how does it differ from Therapeutic Photography? Is Photo- Therapy simply "Art Therapy using photos", or something different? And what, then is "Photo-Art-Therapy"? Is all this confusing? Yes! And in this Article written specifically for an Art Therapy Journal readership, I hope to provide a useful framework for positioning each of these in terms of their relationship to the others, and clarify their similarities and differences, including the areas where they overlap – and explain the criteria used for distinguishing between them. I will explain the "Continuum of Photo-based Therapy Practices" (with PhotoTherapy at one end, and "Therapeutic Photography" at the other) that is in common use around the world for positioning one’s practice so that others will be able to easily understand what it is. I will then locate the sub-category of "Photo-Art-Therapy" from within this context. I will then illustrate with "real-life" examples how I (both a U.S. Registered Art Therapist and Canadian Registered Psychologist) have used my knowledge of Art Therapy theory and practice to enhance the potential effectiveness of my PhotoTherapy work during therapy sessions with clients – in ways that therapists and other mental health professionals who have not been educated about Art Therapy would be unable to do (or understand). By the end of this Article, I hope that readers will recognize that, whether an Art Therapist works from the "art-during-therapy" ("Art Psychotherapy") model of practice or the "art-as-the-therapy-itself" (Therapeutic Art Activities") model, they can benefit from adding PhotoTherapy techniques to their repertoire of adjunctive interventions: using their clients’ own personal snapshots and family photographs (and their interactions with these) to evoke feelings, thoughts, and memories – and related values, beliefs, attitudes, and expectations) in ways not possible when using other art media (or words) alone. After the definitions have been clarified and examples illustrated, the final Section of this Article will provide readers with information about many current practitioners in Spain (and how to contact them), who have long been using photos during their therapy work or as therapeutic/healing activities for self or others. Some are Art Therapists and some are not –and their differences will clearly illustrate the flexibility of the beneficial "partnership" of PhotoTherapy and Art Therapy.